A ketone functionalized luminescent terbium metal–organic framework for sensing of small molecules. Issue 2 (18th November 2014) - Guo, Zhiyong; Song, Xuezhi; Lei, Huaping; Wang, Hailong; Su, Shengqun; Xu, Hui; Qian, Guodong; Zhang, Hongjie; Chen, Banglin
Abstract : A ketone functionalized luminescent terbium metal–organic framework has been realized for the highly selective and sensitive sensing of aniline. Abstract : A ketone functionalized luminescent terbium metal–organic framework has been realized for the highly selective and sensitive sensing of aniline.